Farmer’s Perceptions of Agroforestry Practices, Contributions to Rural Household Farm Income, and Their Determinants in Sodo Zuria District, Southern Ethiopia - Mathewos Tega; Elias Bojago (International Journal of Forestry Research)
Agroforestry has been widely used in developing countries as a solution to mitigate the effects of climate variability. However, its significance to the well-being of farmers in rural communities has not been thoroughly investigated. The purpose of this study was to analyze the contribution of agroforestry practices (AFPs) to the farm income of rural families, the perceptions of farmers, and factors that affect AFPs’ contribution to household income in the Sodo Zuria district. The optimal sample size of 173 households from the three study sites was selected through a stratified random sampling procedure. Data were collected using structured interviews, focus group discussion, observation, and key informant interviews. According to the findings, most farmers in the research area had a good perception of the benefits of agroforestry methods. The yearly mean gross income from various agroforestry approaches was 15,990.90 ETB·ha−1·yr−1 for nonadopters and 32,471.24 ETB·ha−1·yr−1 for adopters, respectively. Tree and fruit tree integration with crops, animals, or pastures has the potential to significantly increase food production and farmer economic situations. Multiple linear regression analysis indicated that the size of the farm, the number of livestock, the experience of agroforestry, and the extension service affect the adoption of agroforestry practices to house farm income positively, while the size of the family negatively affects it. Agroforestry plays a critical role in reducing food poverty and enhancing farmer livelihood resilience (reducing farmers’ vulnerability to climate variability). However, determining the extent to which this is true is challenging because both farmer groups often have low levels of assets such as land and income, which limits tree planting to reaping maximum benefits from agroforestry. As a result, the government and other responsible entities should pay special attention to assisting smallholder farmers in using agroforestry practices for the sustainability of their livelihoods that have been hampered by agricultural land scarcity.